Role of epigallocatechin-3- gallate in the regulation of known and novel microRNAs in breast carcinoma cells - Banerjee, Shrila; Mandal, Abul Kalam Azad (Frontiers in Genetics, 2022)
Breast cancer comprises 30% of all cancer cases among the world's women population. MicroRNAs are small, endogenous, non-coding RNAs that regulate cell proliferating and apoptotic pathways by modulating expressions of related genes. Phytochemicals like epigallocatechin-3-gallate (EGCG) are known to have a chemotherapeutic effect on cancer often through the regulation of microRNAs. The aim is to find out the key known and novel miRNAs, which are controlled by EGCG in breast cancer cell line MDA-MB-231. Next generation sequencing (NGS) revealed 1258 known and 330 novel miRNAs from untreated and 83μM EGCG (IC50 value of EGCG) treated cells. EGCG modulated 873 known and 47 novel miRNAs in the control vs treated sample. The hypothesis of EGCG being a great modulator of miRNAs that significantly control important cancer-causing pathways has been established by analyzing with Kyoto Encyclopedia of Genes and Genomes (KEGG) and Protein Analysis Through Evolutionary Relationships (PANTHER) database. Validation of known and novel miRNA expression differences in untreated vs. treated cells was done using qPCR. From this study, a few notable miRNAs were distinguished that can be used as diagnostic as well as a prognostic marker for breast cancer.